Dispercentiation-Based Diagnostic Assessment Model in Sundanese Language Learning for Junior High School Students in West Java - Kuswari, Usep; Ruhaliah; Haris Santosa Nugraha; Darajat, Danan (CV. Goresan Pena, 2024)
This research is based on the fact that the diagnostic assessment model in Sundanese language learning has not yet been touched upon because the Merdeka Curriculum will only be implemented in 2022. This research aims to describe the grid of the Sundanese language diagnostic assessment model, the diagnostic assessment model in Sundanese language learning, and guidelines for assessment models. Diagnostics in Sundanese language learning are based on the Independent Curriculum, which can provide information for schools regarding content, coverage, format, delivery time, and optimal benefits for learning Sundanese language and literature at the junior high school level in West Java. The method used in this research is a development model using the Research and Development type of research, which aims to produce a product in the form of a diagnostic assessment model in Sundanese language learning because of the Merdeka Curriculum and a diagnostic assessment model guide in Sundanese language learning because of the Merdeka Curriculum at junior high school level in West Java. The research results expected from this research are a grid of diagnostic assessment models in Sundanese language learning because the Merdeka Curriculum has been adapted based on diagnostic assessment models in Sundanese language learning in junior high schools, diagnostic assessment models in Sundanese language learning that have been developed and tested, as well as guidelines for diagnostic assessment models in learning Sundanese at junior high school level in West Java. The output of this research is papers submitted at international meetings, articles published in local journals, and IPR drafts in the form of copyrights.